The Economics of Forest Disturbances Wildfires, Storms, and Invasive Species - Holmes, Thomas P.; Prestemon, Jeffrey P.; Abt, Karen L. (Forestry Sciences, 2008)
This book provides a unique, state-of-the-art review of both traditional and emerging themes in the economics of natural forest disturbances. Although natural disturbances such as wildfire, hurricanes and pests have long been recognized as important factors influencing the structure and health of forests, recent and dramatic increases in the costs and damages associated with forest disturbances necessitates a new evaluation of these processes. The authors show that neo-classical economic principles can be integrated with ecosystem analysis and modern econometric methods to uncover the causes and consequences of natural forest disturbances. The chapters encompass modern areas of concern in forest economics and policy, including temporal and spatial dynamics of economic-ecologic systems, risk-reducing mitigation and adaptation strategies, and the valuation of impacts on market and non-market resources. These topics are developed with case studies demonstrating rigorous empirical analysis with a policy-oriented focus. The book is intended for forest policy analysts and decision-makers, risk managers, forest economists and graduate students studying natural resource economics.